Extraction, entanglements, and (im)materialities: Reflections on the methods and methodologies of natural resource industries fieldwork. (June 2021) - Johnson, Organizing Editors Adrienne; Zalik, Anna; Mollett, Contributors Sharlene; Sultana, Farhana; Havice, Elizabeth; Osborne, Tracey; Valdivia, Gabriela; Lu, Flora; Billo, Emily
This multi-authored collection of papers examines the complex realities of research on natural resource industries, including the messy entanglements of extraction, materiality, and everyday social life this research entails. Of central importance to the contributors is how scholars confront fieldwork challenges ethically, methodologically, and corporeally. The collection has two key objectives. First, it expands our understanding of extractive industry by bringing together work on resources conventionally understood as extractive (e.g. oil and minerals) alongside resource-intensive industries not typically examined through an extractive lens, for instance fisheries, agricultural monocultures, water, and tourism. As such, it considers the historical and current conditions that facilitate the extraction of resources in parallel, cyclical, and reproducing forms. Second, the collection examines scholarly positionalities, methodologies, and dilemmas that arise when studying nature-intensive industries, including the extractive dimensions associated with social research itself. Together, the pieces argue that research concerning extractive industries entails multiple scholarly positions—positions problematically inflected with colonialism and always shaped by power relations. Contributors to the section draw largely from feminist, postcolonial, anti-racist, and historical materialist insights to frame and problematize the corporeal and representational concerns arising from their scholarship on nature-intensive industries, including personal dilemmas that they have encountered in their work. Overall, the collection is driven by the realization that research, and the analyses it entails, may serve as a tool for emancipatory intervention yet also reproduce inequality. The futures of the people and ecosystems at the center of our studies impel constant reflection so that our work, and that of the next generation of scholars, may offer critical analysis that contributes to transforming—rather than reinforcing—oppressive relations associated with extractive sectors and industries.